A construção da identidade profissional de sanitaristas graduados pela Universidade Federal de Mato Grosso - Rossi, Everton (2020)
As from 2008 Graduation Courses in Public Health (hereby CGSC) were created and in the State of Mato Grosso it is offered by the Federal University of Mato Grosso since 2010. With the purpose of the generalist formation, the graduated sanitarian must have the ability to comprehend the phenomenon of the process sickness-health from the collective dimension. The emergence of the CGSC has being putting the matter of the identity of the “new” sanitarian. This study started from the experiences of the egresses of the CGSC of UFMT, having as aim to comprehend elements of their professional identity by the relations with the process of academic formation and the construction of professional identity as workers of the Public Health in Mato Grosso. The data production was through an online questionnaire (Google docs) and by comprehensive interviews guided by a semi-structured thematic script to deepen the matters in the report in the first person. The results were organized in three articulated chapters. One of them brings the motivations to the choice and to the continuity in the graduation in Public Health in which, to the choice, excels the dream and the need to a formation in an university level; the deepening and the improving the knowledge in the field of Public Health by professionals with previous graduation courses and already inserted in the public system of health; by the family tradition; by the affinity with the health area. In the motivations to the continuity in the course, they highlight the will and the fight for a greater quality of the public health; the teaching methodologies adopted during the course (active methodologies); the insertion in the field of internship and extracurricular experiences (extension, research, monitoring). In the other chapter, the basilar notions of Public Health (as a broaden concept of health and the interdisciplinarity) show the potentialities of the course throughout the formation and reflect the professional identity, allowing a broaden and strategic view of the health sector and to comprehend the process sickness/health and its social determiners. Nonetheless, as fragilities, the egresses list the little articulation between the theory and the practice in some of the subjects; the insufficiency of the course load of the internship; the lack of specific components (anatomy, mental health) and the excess of thematic focusing; the lack of the interface of some subjects with the health field. The final chapter emphasizes the identity aspects of the sanitarian as profession, approaching the ways and strategies of insertion of the egresses that are working in the field; the perceptions of what it is to be a sanitarian based in an intersubjective construction, reciprocal and indivisible of Him/Herself and the Other; the future professional expectations that affect the political and institutional dimension of the formalization of the profession by the regulation and its consequences that requires the State acknowledgement. It was concluded that the professional identity is constituted by nonlinear processes and that the insertion in the market does not happen initially, but by the mobilization of forces, being all responsible to engage the fight for acknowledgment. This movement involves the students who are starting the SC, those who already graduated, the teachers, the managers and all of those who define themselves on behalf of and compromise with the improvement of the life quality of the population, the right to the health, the social justice and the strengthening of SUS.